PENDAPATAN PEDAGANG PASAR SENI GUWANG: KAJIAN BERDASARKAN FAKTOR INTERNAL DAN EKSTERNAL - Ida Ayu Nyoman Yuliastuti; Ni Luh Putu Sandrya Dewi (UNHI Press, 2019)
One of the famous art markets in Gianyar Regency is the Guwang Art Market. Along with the development of globalization and competition in the economy, the economic potential of the Guwang Art Market has gradually experienced sluggishness. The Gianyar Regency Government as the manager of the Guwang Art Market and the Guwang Art Market traders must pay attention to internal and external factors that can increase tourist visits to the Guwang Art Market. This study aims to conduct a more in-depth analysis of internal and external factors that can affect the income of the Guwang Art Market traders.The sample in this study consisted of 84 traders from 540 traders in the Guwang Sukawati Art Market, Gianyar Regency. Secondary data was obtained from the Guwang Art Market Administration Office and the primary data was obtained by distributing questionnaires to the Guwang Art Market traders. The analysis technique used is multiple linear regression analysis techniques.